The Benefits of Language Laboratories for Learning Japanese as a Foreign Language - Danaher, Mike; Danaher, Patrick (Language learning journal, 1998)
Considers the pedagogical benefits of a state-of-the-art language laboratory for learners of Japanese. The article argues that, although many believe the language laboratory is anachronistic, it deserves its rightful place as one of the "new" technologies which can enhance foreign-language learning. The benefits, however, are subject to the teacher's ability to encourage within students feelings of confidence & control about using this technology. 1 Table, 18 References. Adapted from the source document